Risk of Active Tuberculosis among Index Case of Householders—A Long‐Term Assessment after the Conventional Contacts Study. Issue 2 (5th July 2016) - Puma, Daniela V.; Pérez‐Quílez, Olga; Roure, Sílvia; Martínez‐Cuevas, Octavio; Bocanegra, Cristina; Feijoo‐Cid, Maria; Valerio, Lluís
Abstract: Objectives: The aim of this study was to determine the incidence of active tuberculosis (TB) among household contacts of TB‐index cases diagnosed during a 7‐year period in a public Primary Care Center located in a high‐incidence area. Design and Sample: A retrospective cohort study was performed. Data collection was based on the capture‐recapture method; the two main sources crossed information from TB‐index and contact cases from the El Fondo Primary Care Center (Santa Coloma de Gramenet, Spain) and their reports to the National Epidemiologic Surveillance Service. Measures: Variables were divided into demographic and health data (result of the Mantoux test, chest X‐ray, presence of risk factors, and indication for chemoprophylaxis). Results: Community nurses identified 103 household contacts that underwent the conventional contact study. Overall, 60.19% were male; the mean age was 29.08 years. Only one case of secondary active TB was found, representing an incidence of 0.56% per TB‐index case and year. Conclusion: The incidence of new secondary TB among household contacts with TB‐index cases was of a case. Nevertheless, a long‐term follow‐up of these householders beyond the conventional contacts study should be considered in areas with higher incidences of TB or among specific high‐risk populations.